2004
DOI: 10.1364/ol.29.002617
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of light propagation in biological tissue

Abstract: We investigated the propagation of light in biological tissues that have aligned cylindrical microstructures (e.g., muscle, skin, bone, tooth). Because of pronounced anisotropic light scattering by cylindrical structures (e.g., myofibrils and collagen fibers) the spatially resolved reflectance exhibits a directional dependence that is different close to and far from the incident source. We applied Monte Carlo simulations, using the phase function of an infinitely long cylinder, to explain quantitatively the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 8 publications
2
75
0
Order By: Relevance
“…A previous model [4] based on Mie scattering of infinite cylinder can produce similar rhombus patterns. However, in their simulation the pattern became elliptic when the measurement location was only ~2 mm away from the light incident point.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A previous model [4] based on Mie scattering of infinite cylinder can produce similar rhombus patterns. However, in their simulation the pattern became elliptic when the measurement location was only ~2 mm away from the light incident point.…”
Section: Discussionmentioning
confidence: 89%
“…This is likely caused by the aforementioned method we applied to handle the fibrous effects, which may only be valid in the diffuse region. Better results might be produced if the cylindrical geometry [4] of muscle fiber is considered. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anisotropic light transfer results from light travelling between discrete tissue layers (i.e. optical boundaries) of different refractive indices, where photons crossing these boundaries are redirected because of Fresnel reflection (Kienle et al, 2004). If photons are travelling at very low angles relative to the boundaries, they can be total internally reflected in cases where tissue layers differ in their refractive index.…”
Section: Research Articlementioning
confidence: 99%
“…Anisotropic directional dependent scattering can for example be modelled by using phase functions derived from an analytical solution of electromagnetic scattering by an infinite cylinder [7]. This was first proposed by Kienle et al [8,9] who observed the anisotropic shapes of backscattered point spread functions (PSF) for different stochastic representations of the cylinder alignments. Similar Monte Carlo simulations have since then been used to model light scattering in anisotropic structures such as biological tissue [10,11], softwood [12] and textile [13].…”
Section: Introductionmentioning
confidence: 99%